2018
DOI: 10.14483/2256201x.12575
|View full text |Cite
|
Sign up to set email alerts
|

Bosque de roble o plantación de coníferas, ¿qué prefieren los líquenes epífitos?

Abstract: Quercus humboldtii es un elemento dominante en los bosques altoandinos de Boyacá, Colombia, el cual, a pesar de ser una especie sombrilla, registra consumos per-cápita de 1300 Kg.año-1 y el remplazo de sus rodales por plantaciones de Pinus patula. Este remplazo afecta las comunidades liquénicas más sensibles. Para rastrear dichas afecciones se examinaron los líquenes en cuatro árboles de cada especie forófita. Cada árbol fue dividido en cinco estratos verticales y se midió la rugosidad, humedad, acidez y lumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
(46 reference statements)
0
4
0
2
Order By: Relevance
“…The structure of the substrate, such as its humidity, texture, pH, host species and tree age, bark fissuring (BF), circumference of the stem at breast height (CBH) [29][30][31][32][33] (Table 1), and characteristics of the environment (illuminance, conservation, disturbance, and alterations), may also affect the occurrence of corticolous lichen [34,35]. The influence of these factors on the morphotype richness, diversity, or abundance of lichen is typically evaluated through the application of an Analysis of Variance (ANOVA) or Generalized Linear Models (GLMs).…”
Section: Introductionmentioning
confidence: 99%
“…The structure of the substrate, such as its humidity, texture, pH, host species and tree age, bark fissuring (BF), circumference of the stem at breast height (CBH) [29][30][31][32][33] (Table 1), and characteristics of the environment (illuminance, conservation, disturbance, and alterations), may also affect the occurrence of corticolous lichen [34,35]. The influence of these factors on the morphotype richness, diversity, or abundance of lichen is typically evaluated through the application of an Analysis of Variance (ANOVA) or Generalized Linear Models (GLMs).…”
Section: Introductionmentioning
confidence: 99%
“…The latter has since broadly promoted lichenology in the country through the Grupo Colombiano de Liquenología (GCOL; http://licbiologia.udistrital.edu. co:8080/grupo-colombiano-de-liquenologia), with a large number of thesis works at the undergraduate, master, and even doctoral level at various universities completed and in part published (Ardila-Ríos et al 2015;Díaz-Escandón et al 2015;Ramírez-Morán et al 2016;Simijaca et al 2018;Motta et al 2019). Similar examples of benefitsharing for capacity building could be given for other lichenologists in Brazil (Cáceres et al 2007;Kirika et al 2017;Menezes et al 2018), Mexico (Herrera-Campos et al 1998, Costa Rica (Umaña & Sipman 2002;Chaves et al 2004), Peru (Rivas Plata & Lumbsch 2011), Bolivia (Flakus & Printzen 2014), Kenya (Kirika et al 2017(Kirika et al , 2019, Sri Lanka (Weerakoon et al 2012, Thailand (Boonpragob et al 1998;Homchantara & Coppins 2002;Papong et al 2009;Kraichak et al 2015), among many others.…”
Section: Three Challenges To Contemporaneous Taxonomymentioning
confidence: 99%
“…Several studies have revealed strong relationships among substrate features and species richness or lichen community composition, which are influenced by climatic and substrate features (Cáceres et al 2007; Rosabal et al 2013), which have effects on lichen community diversity (Wolf 1994; Boonpragob & Polyiam 2007; Zárate-Arias et al 2019). This sensitivity has allowed the use of lichens as indicators of forest continuity (McCune 2000; Rivas-Plata et al 2008; Benítez et al 2015), successional stages (Hedenås & Ericson 2000; Nordén et al 2012), and the effect of alien tree species on the richness and composition of lichens (Käffer et al 2009, 2010, 2011; Calviño-Cancela et al 2013; Ardila et al 2014; Simijaca et al 2018).…”
Section: Introductionmentioning
confidence: 99%